2011
DOI: 10.1111/j.1439-0507.2010.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungal adherence to plasma‐modified polymethylmethacrylate

Abstract: There is a propensity for fungal adherence to the polymethylmethacrylate used for making denture bases. Therefore, this study investigated whether surface modifications with plasma treatments would reduce the adherence of Candida albicans to a denture base resin. Samples (n = 180) with smooth and rough surfaces were made and divided into five groups: control - non-treated; experimental groups - submitted to plasma treatments to obtain surfaces with different hydrophobicities (Ar/50 W; ArO(2) /70 W; AAt/130 W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 46 publications
3
38
0
4
Order By: Relevance
“…Surface characteristics of denture base acrylic resin, such as surface roughness, hydrophilicity, surface topography, and surface charge have all been reported to involved in the adherence of Candida, which is the essential step for development of Candida-associated denture stomatitis [7][8][9][10][11] . There has been a large body of evidence indicating that atmospheric pressure cold plasma technique may affect these surface characteristics on the surface layer without affecting their bulk properties 7,11,12,[20][21][22][23] . The results of the present study revealed that cold plasma treatment of acrylic resin specimens significantly increased the surface hydrophilicity when comparing with the control group thus confirmed the findings of published investigations 7,11,12,21,23) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surface characteristics of denture base acrylic resin, such as surface roughness, hydrophilicity, surface topography, and surface charge have all been reported to involved in the adherence of Candida, which is the essential step for development of Candida-associated denture stomatitis [7][8][9][10][11] . There has been a large body of evidence indicating that atmospheric pressure cold plasma technique may affect these surface characteristics on the surface layer without affecting their bulk properties 7,11,12,[20][21][22][23] . The results of the present study revealed that cold plasma treatment of acrylic resin specimens significantly increased the surface hydrophilicity when comparing with the control group thus confirmed the findings of published investigations 7,11,12,21,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Surface characteristics, such as surface roughness, hydrophilicity, and surface charge have all been reported to involve in the adherence of Candida [7][8][9][10][11] . Therefore, the development of methods that could modify these denture base surface properties to prevent the adherence of C. albicans would be a significant advancement in the prevention of Candida-associated denture stomatitis 8,9,12) . Atmospheric pressure cold plasma is a complex mixture composed of ions, energetic free radicals, electrons, atoms, and molecules generated by gas discharge.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations